A real-world pharmacovigilance analysis for transthyretin inhibitors: findings from the FDA adverse event reporting database - Liu, Yuan; Li, Hao; Hu, Cheng; Tan, Li; Yin, Ping; Li, Zhihao; Zhou, Shuangshan; Su, Li (Frontiers in Pharmacology, 2024)
Objective：The purpose of this study is to investigate the drug safety of three Transthyretin (TTR) inhibitors in the real world using the United States Food and Drug Administration Adverse Event Reporting System(FAERS) database. Methods:This study extracted reports received by the FAERS database from the first quarter of 2018 to the third quarter of 2023 for descriptive analysis and disproportionality analysis. Safety signal mining was conducted at the Preferred Term (PT) level and the System Organ Class (SOC) level using reporting odds ratio (ROR). The characteristics of the time-to-onset curves were analyzed using the Weibull Shape Parameter (WSP). The cumulative incidence of TTR inhibitors was evaluated using the Kaplan-Meier method. Subgroup analyses were conducted based on whether the reporter was a medical professional. Results:A total of 3,459 reports of adverse events (AEs) caused by TTR inhibitors as the primary suspect (PS) drug were extracted. The top three reported AEs for patisiran were fatigue, asthenia, and fall, with the most unexpectedly strong association being nonspecific reaction . The top three reported AEs for vutrisiran were fall, pain in extremity and malaise, with the most unexpectedly strong association being subdural haematoma. The top three reported AEs for inotersen were platelet count decreased, blood creatinine increased, and fatigue, with the most unexpectedly strong association being blood albumin decreased. Vitamin A decreased, arthralgia, and dyspnea were the same AEs mentioned in the drug labels of all three drugs, while malaise and asthenia were the same unexpected significant signals. This study offers evidence of the variability in the onset time characteristics of AEs associated with TTR inhibitors, as well as evidence of differences in adverse event reporting between medical professionals and non-medical professionals. Conclusion：In summary, we compared the similarities and differences in drug safety of three TTR inhibitors in the real world using the FAERS database. The results indicate that not only do these three drugs share common AEs, but they also exhibit differences in drug safety profiles. This study contributes to enhancing the understanding of medical professionals regarding the safety of TTR inhibitors.